RIVALITAS POLITIK LOKAL Perspektif Sosiologi Kekuasaan atas Hegemoni Parpol Terhadap Calon Perseorangan dalam Pemilihan Walikota Kendari 2012 - Ambo Upe (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
The Region head elections have been undergone changes significant towards consolidation democrace, it is began from the representation system, the directly elections with giving chance for the politics the couple of independent candidate. The fenomena of the independent candidate at the new local politics area have began in the fith years late. So the sociological studies regard with the politics revility its limited. Therefore it is not found yet the scientific publication held. So this study aims to explain the construction of the politics party hegemony of the independent candidates and to understand the voters tendention in occur the politics revality at the Kendari Mayor elections in the years 2012. To achieve the aims is used the qualitative descriptive approach that based in the natural background and the politics setting in Kendari City. The result of this research showed the couple victory Asrun Musadar that to discrip the manifestation of the hegemony counstruction of the politics party and the incumbent politics party structuration. Beside that the couple of La Ode Geo- Oscar Silverius as the independent candidate failure in the hegemony counter that coused by the internalisation politics was not optimally and the institutional is not force to the lowers people organization. Moreever the couple candidate independent failure its also coused by the vouters tendention of election that have been hegemony by the politics party persuasived. Thus the conclution of this case are the politics revality in region heads elections is following with the pattern dialectically include; the hegemony, counter hegemony, new hegemony, and the re-counter hegemony and so on.Keywords: Election, Local Politic, Hegemony, Politic Party, Independent Candidates